Efektivitas Pembelajaran Matematika SMA Berbantuan Media YouTube dan Quiziz Pada Materi Program Linear - Setyo, Arie Anang; Yuliani, Nova; Situmorang, Helena; Ferneyanan, Rianti; Saefudin, Mohammad (Jurnal PEKA (Pendidikan Matematika), 2026)
ABSTRACT: This study investigates the effectiveness of integrating YouTube learning videos with Quizizz-based evaluation in supporting senior high school students’ interest and achievement in Linear Programming. The research applied a quantitative method using a One-Shot Case Study design. In this approach, students first accessed instructional material through YouTube videos and then completed an online assessment through the Quizizz platform. The participants were selected purposively from students who had previously studied the topic of Linear Programming to ensure that the instructional materials were relevant to their prior understanding. The data consisted of students’ scores obtained from the Quizizz evaluation, which were analyzed using descriptive statistical techniques to describe the level of students’ learning performance. The results reveal that the use of YouTube-based instruction did not significantly improve students’ learning interest or academic outcomes. This condition can be observed from the evaluation scores, which remained relatively low after the learning intervention. The findings suggest that the use of YouTube videos as the primary instructional resource alone is not sufficient to maximize learning effectiveness. Therefore, additional instructional support, such as teacher guidance or the incorporation of more interactive learning strategies, is recommended to improve students’ learning performance.